Implementasi Pendekatan Jurimetri dalam Penyelesaian Sengketa Hak-Hak Perempuan dalam Putusan Cerai Talak - Muhamad Faudzan; Erina Pane; Linda Firdawaty (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The divorce gives rise to rights and obligations, especially women's economic rights after divorce, namely iddah, mut'ah and madhiyah livelihood. Judges in determining the amount of alimony still vary and there are no standard rules and methods so that judges can guide them in determining the value of alimony for wives as a result of divorce which reflects propriety and justice. The author will put forward the idea of ​​the jurimetric method as a mathematical analysis method related to determining the amount of iddah, mut'ah and madhiyah maintenance for wives after divorce. The aim of the research is to analyze the application of the jurimetric approach in resolving disputes over women's rights in divorce decisions for talak at the Gedong Tataan Religious Court and the Sukadana Religious Court and to analyze the perspective of maslahah al mursalah and the theory of justice towards the implementation of the jurimetric approach as a method for determining the amount of women's rights in decisions divorce. This research is normative legal or normative juridical research which is descriptive analytical in nature. The application of jurimetry in determining the amount of women's rights in divorce and divorce decisions regarding 'iddah, mut'ah and madhiyah income, is carried out by collecting empirical data which is then expressed in variables. Jurimetry is a tool to interpret norms for the sake of realizing justice. By applying a jurimetric approach in determining the amount of 'iddah, mut'ah and madhiyah income, it has fulfilled procedural justice and distributive justice and fulfilled maslahah al-mursalah.